Adaptive memory: enhanced source memory for animate entities. Issue 8 (14th September 2019) - Mieth, Laura; Röer, Jan Philipp; Buchner, Axel; Bell, Raoul
ABSTRACT: The animacy effect refers to enhanced memory for animate over inanimate items. In two studies, we examined whether this memory advantage generalises to source memory. A multinomial processing tree model was used to disentangle item recognition, source memory, and guessing processes. In Study 1, animate and inanimate words were presented at different spatial locations on the screen. Animacy was associated with enhanced source memory for the spatial locations of the items. In Study 2, pseudowords were associated with animate and inanimate properties. Replicating previous results, the pseudowords were better remembered when they were associated with animate properties than when they were associated with inanimate properties. What is more, participants had enhanced source memory for the association between the pseudowords and the animate properties. The results strengthen the idea that animate items are associated with richer mnemonic representations than inanimate items.